Zygomaticomaxillary Complex Fracture Repositioning Using Plates and Screws: Standard Techniques, Modifications, and Cost‑Effectiveness Considerations - Iwan Setiawan Adji; Zerlina Norberta Ramadhani; Arum Widya Anantasya; Ardhini Tyas Megaranti; Gavin Editya Mukti; Mohammad Alifiya Devano (FORIKES, 2026)
Iwan Setiawan Adji1, Zerlina Norberta Ramadhani2, Arum Widya Anantasya2, Ardhini Tyas Megaranti2, Gavin Editya Mukti2, Mohammad Alifiya Devano21Department of Otorhinolaryngology–Head and Neck Surgery, Kartini Regional General Hospital, Karanganyar, Indonesia; 2Medical Professional Education Program, Universitas Muhammadiyah Surakarta, Sukoharjo, IndonesiaCorrespondence: Zerlina Norberta Ramadhani: Kampus IV UMS, Jl. Ahmad Yani, Tromol Pos 1, Pabelan, Kartasura, Sukoharjo; norbertazr@gmail.com ABSTRACT Zygomaticomaxillary complex (ZMC) fractures are among the most common midfacial injuries and may compromise both facial aesthetics and functional outcomes. Although traditional management recommends multipoint fixation to restore stability, emerging evidence suggests that minimal fixation may achieve comparable clinical results with greater procedural efficiency. This systematic review aims to evaluate the clinical outcomes and cost‑effectiveness of one‑point, two‑point, and three‑point fixation techniques in the management of ZMC fractures. This review was conducted following the PRISMA 2020 guidelines. A systematic search was performed in PubMed, ScienceDirect, Google Scholar, and ResearchGate. Eighteen studies evaluating plate‑and‑screw fixation techniques were included and analyzed qualitatively. Outcomes assessed included postoperative stability, facial symmetry, orbital function, complication rates, operative time, implant use, and overall treatment cost. One‑point and two‑point fixation demonstrated postoperative stability, facial symmetry, and orbital function comparable to three‑point fixation when adequate anatomical reduction was achieved. Complication rates were low and showed no meaningful differences among fixation techniques. Minimal fixation was associated with shorter operative time, reduced implant use, and lower overall treatment costs. Efficiency gains were primarily attributed to decreased surgical duration and fewer required implants. Clinical outcomes were more strongly influenced by the quality of reduction and the strategic selection of fixation points than by the number of fixation sites. In conclusion, one‑point and two‑point fixation represent safe and effective alternatives to traditional multipoint fixation for selected ZMC fractures, offering optimal clinical outcomes while improving procedural efficiency and cost‑effectiveness.Keywords: zygomaticomaxillary complex fracture; internal fixation; one‑point fixation; two‑point fixation; cost‑effectiveness